First Records of Non-Native Eurasian Wild Boar Sus Scrofa (Linnaeus, 1758 (Mammalia: Artiodactyla) in a Coastal Ecosystem of Temperate Forest of South-Central Chile - Moreira-Arce, D (REGIONAL EURO-ASIAN BIOLOGICAL INVASIONS CENTRE-REABIC, 2020)
We report the first casual record of Eurasian wild boar Sus scrofa in Nahuelbuta Mountain Area. located in the coastal Temperate Forest of south-central Chile. Camera-trapping was conducted between January 2018 and February 2019 at two sites comprised by native native forest and commercial tree plantations. Wild boars were detected within plantations of Monterey pine mainly during Austral summer (December to February). daytime (between 11:00 and 20:00) and close (3 km) to Nahuelbuta National Park. The combination of its highly adaptable generalist behaviour and the extensive presence of commercial tree plantations in Nahuelbuta Mountain Area may favour the expansion of the invasive wild boar throughout this imperilled ecosystem, including its potential occurrence within the small and isolated protected areas present in it.